Sensitivity of Hartmannella (Acanthamoeba) to 5-fluorocytosine, hydroxystilbamidine, and other substances - Casemore, David P. (1970)
The effect of 24 anti-amoebic and other chemotherapeutic compounds on six strains of hartmannellid amoebae was studied by tissue culture, agar diffusion, and liquid axenic culture. Of the recognized anti-amoebic compounds only one inhibited growth of the amoebae, which were remarkable for their resistance. Two compounds, hydroxystilbamidine isethionate and 5-fluorocytosine, showed some amoebicidal activity while some others were inhibitory.